2016
DOI: 10.1016/j.bmc.2015.11.038
|View full text |Cite
|
Sign up to set email alerts
|

The indole alkaloid meleagrin, from the olive tree endophytic fungus Penicillium chrysogenum, as a novel lead for the control of c-Met-dependent breast cancer proliferation, migration and invasion

Abstract: Fungi of the genus Penicillium produce unique and chemically diverse biologically active secondary metabolites, including indole alkaloids. The role of dysregulated hepatocyte growth factor (HGF) and its receptor, c-Met, in the development and progression of breast carcinoma is documented. The goal of this work is to explore the chemistry and bioactivity of the secondary metabolites of the endophytic Penicillium chrysogenum cultured from the leaf of the olive tree Olea europea, collected in its natural habitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 41 publications
3
28
0
Order By: Relevance
“…Meleagrin (2) exhibited the best growth-inhibitory activity against two different leukemia cells (K562 and HL-60) with IC 50 values of 8.9 and 12.7 μM. A similar level of antineoplastic activity was reported by Mady et al [ 38 ], in which meleagrin (2) showed significant inhibitory activities against the proliferation and migration of c-Met-dependent breast malignancy. Roquefortine alkaloids (3,4) showed a medium antibacterial activity against Gram-negative bacterium Escherichia coli and Gram-positive bacterium Staphylococcus aureus .…”
Section: Resultssupporting
confidence: 70%
“…Meleagrin (2) exhibited the best growth-inhibitory activity against two different leukemia cells (K562 and HL-60) with IC 50 values of 8.9 and 12.7 μM. A similar level of antineoplastic activity was reported by Mady et al [ 38 ], in which meleagrin (2) showed significant inhibitory activities against the proliferation and migration of c-Met-dependent breast malignancy. Roquefortine alkaloids (3,4) showed a medium antibacterial activity against Gram-negative bacterium Escherichia coli and Gram-positive bacterium Staphylococcus aureus .…”
Section: Resultssupporting
confidence: 70%
“…Since tumor recurrence is a manifestation of the resistance of many cancers to clinically used chemotherapeutic agents, we next examined the efficacy of N. sphaerica crude extracts to inhibit lung cancer and glioblastoma cell migration. Boyden chamber assays revealed that cells treated with 2 µg/ml of N. sphaerica crude extracts decreased (P < 0.05) tumor cell migration as compared to vehicle-treated control cells [ Figure 7], paralleling recent findings by Mady et al [22] that showed the endophytic fungus Penicillium chrysogenum impaired breast cancer cell migration.…”
Section: Resultssupporting
confidence: 81%
“…78 By coupling this derivatization strategy with the broad substrate scope of OxaD, we have established a platform in which novel indole alkaloid frameworks can be paired with an array of dipolarophiles in a cycloaddition cascade. Recent reports describing the therapeutic potential of 2 29 and 3 27,30 provide strong motivation to develop these tools. Future efforts in our laboratories will also seek to extend the substrate scope of OxaD beyond alkaloids in the roquefortine family.…”
Section: Discussionmentioning
confidence: 99%